2003
DOI: 10.1515/cclm.2003.023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiple Cytokines by Protein Arrays from Cell Lysate and Tissue Lysate

Abstract: Previously we demonstrated that multiple cytokines could be simultaneously detected using an antibody-based protein array system with high sensitivity and specificity from conditioned medium and serum. Here, we created a higher density array system to simultaneously detect 35 cytokines from cell lysates and tissue lysates. This assay combines the advantages of the specificity of enzyme-linked immunosorbent assays (ELISA), sensitivity of enhanced chemiluminescence (ECL), and high-throughput of microspot. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…By multiplexing antibody-based methods through bead-based or microarray-based formats, multiple proteins may be assayed in parallel with lowered consumption of samples and reagents. The application of antibody microarray methods to cancer research has been shown in studies on proteins in sera (1)(2)(3)(4)(5), cell culture (6,7), and resected tissue samples (8)(9)(10). These studies have shown the feasibility and promise of the technology, but the application to molecular profiling and biomarker development has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…By multiplexing antibody-based methods through bead-based or microarray-based formats, multiple proteins may be assayed in parallel with lowered consumption of samples and reagents. The application of antibody microarray methods to cancer research has been shown in studies on proteins in sera (1)(2)(3)(4)(5), cell culture (6,7), and resected tissue samples (8)(9)(10). These studies have shown the feasibility and promise of the technology, but the application to molecular profiling and biomarker development has yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Two-color comparative fluorescence analyses can compare protein changes of 2 experimental conditions associated with disease progression or drug effects (43,44 ). Cytokine profiles of cell lysates have also been compared with those obtained from body fluids and tissue extracts (47 ). The use of Clinical Chemistry 52, No.…”
Section: Cell Culturementioning
confidence: 99%
“…9, 2006 antibody arrays for high-throughput profiling of cultured cells can be useful to evaluate signaling pathways including tyrosine kinase networks (45 ). Forward and reverse arrays can assess the presence of phosphorylated and unphosphorylated forms of proteins, if adequate antibodies are available to address specific posttranslational modifications of target proteins (10,14,46,47 ). Antibody arrays can profile enzyme activities in protein extracts and cell culture supernatants and can provide a convenient platform to evaluate activity-based protein profiling with high sensitivity and specificity and less sample consumption than initial gel-based strategies for assessing the functional state of enzymes.…”
Section: Cell Culturementioning
confidence: 99%
“…This assay format is a relatively simple and very convenient way of simultaneously analyzing a sample for many different analytes, and this method of highly parallel testing is more rapid than serial assays. At the forefront of emerging tests that are suited to a microarray format are tests for assessing drug metabolizer status (e.g., CYP450 genotyping) [33], evaluating drug resistance by human immunodeficiency virus (HIV) [34], detecting diseasecausing mutations (e.g., cystic fibrosis, p53) [35,36], resequencing [37,38], detecting SNPs [37][38][39], measuring cytokines [23,24], and assessing allergic responses [25][26][27][28].…”
Section: Transition Of Microarray Tests From Research Into Routine CLmentioning
confidence: 99%
“…Reagents immobilized in an array format include cDNA, oligonucleotides, peptide nucleic acids [1][2][3][4][5][6][7][8], antibodies, and antigens [9][10][11][12][13][14][15][16][17][18]. The major research applications for DNA arrays have been expression monitoring and sequencing [19][20][21][22], and prominent applications for protein arrays include simultaneous cytokine analysis [23,24], allergen testing [25][26][27][28], and studies to discover markers for disease diagnosis and management [18].…”
Section: Introductionmentioning
confidence: 99%